Analysis of Viral Marketing on Purchasing Decisions 0n Skincare Through Brand Image as an Intervening Variable - Citradewi, Any; Komariah, Kokom; Saori, Sopyan (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study examines the effect of Viral Marketing on purchasing decisions for Skintific Skincare products with Brand Image as an intervening variable. This study focuses on Skintific users in Sukabumi City, using a quantitative approach with descriptive causal method. Data was collected through questionnaires from 180 respondents selected using purposive sampling technique. Data analysis was conducted using SEM-PLS method. The results showed that Viral Marketing has a significant influence on Brand Image (R²=0.608) and purchasing decisions (R²=0.791). Viral Marketing dimensions, such as information clarity and content attractiveness, contribute positively to improving Brand Image and purchasing decisions. Brand Image also has a significant effect on purchasing decisions, strengthening consumer confidence in the product. However, Brand Image does not effectively mediate the relationship between Viral Marketing and purchasing decisions because the direct effect of Viral Marketing on purchasing decisions is greater than the indirect effect through Brand Image. This study suggests optimizing viral marketing strategies through informative and interesting content on social media and increasing direct interaction with consumers to strengthen brand image and loyalty. This research contributes to digital marketing literature and marketing management practices to improve the effectiveness of marketing strategies in the digital era.